2017
DOI: 10.1590/s1984-29612017031
|View full text |Cite
|
Sign up to set email alerts
|

First report of scuticociliatosis caused by Uronema sp. in ornamental reef fish imported into Brazil

Abstract: Scuticociliatosis, which is caused by an opportunistic ciliate protozoan, is responsible for significant economic losses in marine ornamental fish. This study reports the occurrence of Uronema sp., which was found to be parasitizing three species of marine reef fish imported into Brazil and maintained in quarantine: Vanderbilt's Chromis (Chromis vanderbilti), blue-green damselfish (Chromis viridis), and sea goldie (Pseudanthias squamipinnis). During the quarantine period, some fish presented with behavioral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Azad et al (2007) also reported necrotic degeneration of the gill epithelium, eroded dermal epithelium and liquefied necrotic degeneration by inflammatory cells (monocytes, macrophages, and thrombocytes) of the underlying musculature, clogging of the kidney tubules, severe necrosis of the tubular and collecting ducts epithelium, sloughed intestinal mucosal epithelium with cell debris in the intestinal lumen, degeneration of the stomach musculature, necrotic degeneration of the epithelium of intestinal microvilli, and complete loss of mucosal epithelium of the stomach, which were also found in the current study. Cardoso et al (2017) recently described histopathological lesions similar to our findings here found. These authors reported invasion of scuticociliates in the skin layers, compromising the skeletal muscle, hemorrhages, inflammation composed by mononuclear and granular cells in the skeletal muscle, cutaneous necrosis, muscle fiber edema, and necrotizing myositis, necrosis of the secondary lamellae and inflammatory infiltration of eosinophilic granulocytes in the gills, and inflammatory infiltration of eosinophilic granulocytes in the renal capsule.…”
Section: Discussionsupporting
confidence: 92%
“…Azad et al (2007) also reported necrotic degeneration of the gill epithelium, eroded dermal epithelium and liquefied necrotic degeneration by inflammatory cells (monocytes, macrophages, and thrombocytes) of the underlying musculature, clogging of the kidney tubules, severe necrosis of the tubular and collecting ducts epithelium, sloughed intestinal mucosal epithelium with cell debris in the intestinal lumen, degeneration of the stomach musculature, necrotic degeneration of the epithelium of intestinal microvilli, and complete loss of mucosal epithelium of the stomach, which were also found in the current study. Cardoso et al (2017) recently described histopathological lesions similar to our findings here found. These authors reported invasion of scuticociliates in the skin layers, compromising the skeletal muscle, hemorrhages, inflammation composed by mononuclear and granular cells in the skeletal muscle, cutaneous necrosis, muscle fiber edema, and necrotizing myositis, necrosis of the secondary lamellae and inflammatory infiltration of eosinophilic granulocytes in the gills, and inflammatory infiltration of eosinophilic granulocytes in the renal capsule.…”
Section: Discussionsupporting
confidence: 92%
“…Freshwater bathing was previously performed successfully in the cage-farmed cobia, Rachycentron canadum, parasitized by N. melleni (MOREIRA et al, 2013). The success of prognosis is even greater when the fish are maintained under optimal water quality conditions and fed with balanced diet (CARDOSO et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They are subjected to high tributary load of importation and international transport, which enhance the costs of each batch of fish. In order to minimize the economic losses and mortality with parasitic diseases, and to promote fish welfare, it is necessary to take care of the fish until the fish are sold (CARDOSO et al, 2017). Appropriate quarantine period, handling by trained professionals, early diagnosis, and preventive treatment of some parasites, such as N. melleni, are important for maintaining the fish in aquarium and minimizing the risk of introduction of transboundary diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the import and international transportation of these fish is costly, which increases the costs of each batch of fish. In order to minimize the economic losses and mortality due to parasitic diseases, and to promote fish welfare, it is necessary to take care of the fish until they are sold (CARDOSO et al, 2017(CARDOSO et al, , 2019. In this report, white spot disease was detected early in yellowtail tangs, and the efficacy of the Seachem Cupramine  treatment was demonstrated, which avoided losses of fish due to mortality.…”
Section: Introductionmentioning
confidence: 90%